2005
DOI: 10.1007/s00431-005-1630-2
|View full text |Cite
|
Sign up to set email alerts
|

Is urorectal septum malformation sequence a variant of the vertebral defects, anal atresia, tracheo-oesophageal fistula, renal defects and radial dysplasia association? Report of a case and a review of the literature

Abstract: Although defects of the urorectal septum malformation sequence and the vertebral defects, anal atresia, tracheo-oesophageal fistula, renal defects and radial dysplasia association overlap, we believe that they are separate entities. Differentiating the urorectal septum malformation sequence from vertebral defects, anal atresia, tracheo-oesophageal fistula, renal defects and radial dysplasia association is helpful to develop appropriate clinical investigations and search for the aetiology and pathogenesis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Therefore, it was difficult to diagnose the present case as a cloacal exstrophy variant based only on prenatal knowledge of a spinal defect. As a result, a misdiagnosis of URSMS was made due to the presence of defects in the internal and external genitalia without omphalocele (9,10). There is widespread agreement that the infra-umbilical wall defect is the predominant difference between the two diseases as the accepted mechanism of cloacal exstrophy is the failure of the primitive streak mesoderm to extend into the infra-umbilical cloacal membrane, resulting in the incomplete formation of the lower abdominal wall and omphalocele (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was difficult to diagnose the present case as a cloacal exstrophy variant based only on prenatal knowledge of a spinal defect. As a result, a misdiagnosis of URSMS was made due to the presence of defects in the internal and external genitalia without omphalocele (9,10). There is widespread agreement that the infra-umbilical wall defect is the predominant difference between the two diseases as the accepted mechanism of cloacal exstrophy is the failure of the primitive streak mesoderm to extend into the infra-umbilical cloacal membrane, resulting in the incomplete formation of the lower abdominal wall and omphalocele (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…After the first description of complete URSM sequence by Escobar et al. (1987), to date, 73 cases of complete and more than 25 cases of partial URSM sequence have been reported (Chien et al. 2005; Patil & Phadke 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, partial and full URSM sequences should be considered as separate conditions from VATER association as these are not only distinct abnormalities, but the prognoses in these sequences are markedly different from that for VATER association. Chien et al. (2005) found that patients with URSM spectrum have a significantly higher prevalence of urinary tract defects, anal atresia, and anomalies of the genitalia than patients with VATER association.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Escobar et al [10] reported a URSMS case and discussed its etiology. Still, we should be careful in concluding whether the etiology of URSMS is exactly related to gene expression abnormalities caused by some teratogens or a gene mutation itself [11] . This issue should be clarified in the future by more specific evidence.…”
Section: Discussionmentioning
confidence: 99%